Pengembangan Media Pembelajaran Interaktif Berbasis Android Menggunakan iSpring Untuk Materi Penyajian Data Di Kelas VII Sekolah Menengah Pertama - Nery, Rieno Septra; Sunardi, Sunardi; Aprizal, Aprizal (Universitas Muhammadiyah Palembang, 2021)
This study aims to produce android-based interactive learning media for data presentation material in class VII Junior High School that is valid, practical and has a potential effect on student learning outcomes. The research used is development research (Development Research). The subjects in this study were 7th graders of SMP XX in Palembang, totaling 35 students. Based on the results of the study, it was found that the media developed was valid, practical and had a potential effect. Validity can be seen from the results of the assessment of experts (material, media, and language) who get an accumulated score of 155 from a maximum score of 168 with a percentage result of 92.26%. In the one to one stage, it was also declared valid as seen from the results of the questionnaire where a score of 52 was obtained from the maximum score of 60 with a percentage of 86.66%. The practicality of the learning media that has been developed is seen from the trials at the small group stage with a score of 286 from the maximum score of 300 with a percentage result of 95.33% and it can be categorized that the media developed is practical. From the results of the analysis that has been carried out that the average final score of students is 72.85, which means that student learning outcomes are classified as good, it can be concluded that interactive learning media has been developed to have a potential effect on student learning outcomes